PERANCANGAN BUKU ILUSTRASI MENGENAI PEMBUATAN WAYANG GOLEK UNTUK ANAK USIA 9 – 12 TAHUN DI JELEKONG - Utami, Giva Dini; Nastiti, Nisa Eka; Alifaprilina Supriadi, Olivine (Telkom University, 2024)
Wayang Golek is one of the arts preserved in Jelekong. However, the number ofwayang golek craftsmen in Jelekong actuallydecreased from year to year due to the lackof interest of the younger generation. As for introducing and educating the making of theoriginal Jelekong golek puppets, one of them is to create educational media in the form ofpicture storybooks with illustrations that are suitable for children to read. The purpose ofthis study is to find out the design ofeducational media in the form of illustrated booksabout making wayang golek by utilizing proper visualization so that theycan know andpreserve the original wayang golekJelekong. Research data were collected through directobservation toJelekong, interviews with related resource persons, and literature studiesusing qualitative research methods. Keywords: Wayang Golek Jelekong, wayang golek craftsmen, educational media, illustration.